The Role of Spiritual Intelligence in the Religious Life of Catholic Nuns: A Religious Psychology Perspective - Theodosia Yosephina Palma; Augustina Sulastri; Cicilia Tanti Utami (Eduvest - Journal of Universal Studies, 2026)
This paper examines the role of spiritual intelligence in sustaining the religious life of Catholic nuns from the perspective of religious psychology. Monastic life demands psychological fortitude, spiritual commitment, and adaptive ability in community dynamics and pastoral ministry. However, previous studies have tended to highlight resilience, religious experience, or emotional intelligence, while the contribution of spiritual intelligence has rarely been explored empirically. Source searches were conducted on the Scopus, Google Scholar, and Garuda databases with the keywords spiritual intelligence, religious life, Catholic nuns, and psychological resilience. Out of the initial 50 documents, 17 articles were selected according to the inclusion criteria and analyzed using the thematic approach of Braun and Clarke (2006). The synthesis of literature produces four main themes. First, spiritual intelligence becomes a source of meaning in life through the appreciation of religious vows, the practice of spiritual reflection, and pastoral service. Second, spiritual intelligence aids emotional–spiritual integration in the community by emphasizing prayer, reflection, and forgiveness to manage interpersonal conflicts. Third, spiritual intelligence encourages pastoral ministry as a form of personal relationship with God, not just an institutional obligation. Fourth, spiritual intelligence strengthens psychological resilience through the process of meaning-making and transcendence of self that allows nuns to transcend the ego and discover the depth of meaning of life. This study affirms spiritual intelligence as an important determinant of the quality of religious life and provides practical implications for Catholic nuns' formation programs that integrate spiritual and psychological formation.